2016
DOI: 10.1007/s00167-016-4022-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a virtual reality-based simulator for shoulder arthroscopy

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 43 publications
4
34
0
Order By: Relevance
“…The studies were broadly split into 3 categories: studies measuring the impact of a simulation training intervention (26 studies 6 - 31 ), studies assessing the construct validity of a simulator designed for training surgeons (42 studies 32 - 73 ), and studies validating an assessment tool (37 studies 74 - 110 ) (see Appendix Tables 1 and 2, column 1). Of the included studies, 60% assessed arthroscopic skill involving the knee (34 studies) 6 , 8 , 9 , 13 , 15 , 17 , 19 , 31 - 33 , 36 , 38 , 39 , 41 , 42 , 47 , 48 , 54 - 56 , 63 , 74 , 75 , 77 - 83 , 86 , 87 , 89 , 91 , the shoulder (25 studies) 7 , 12 , 15 , 16 , 18 , 20 , 37 , 40 , 44 , 45 , 49 , 51 , 53 , 54 , 56 , 63 , 76 , 77 , 81 , 82 , 88 , 90 - 92 , 110 , the hip (3 studies) 43 , 50 , 85 , the ankle (1 study) 14 , and basic general arthroscopic skills (6 studies)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were broadly split into 3 categories: studies measuring the impact of a simulation training intervention (26 studies 6 - 31 ), studies assessing the construct validity of a simulator designed for training surgeons (42 studies 32 - 73 ), and studies validating an assessment tool (37 studies 74 - 110 ) (see Appendix Tables 1 and 2, column 1). Of the included studies, 60% assessed arthroscopic skill involving the knee (34 studies) 6 , 8 , 9 , 13 , 15 , 17 , 19 , 31 - 33 , 36 , 38 , 39 , 41 , 42 , 47 , 48 , 54 - 56 , 63 , 74 , 75 , 77 - 83 , 86 , 87 , 89 , 91 , the shoulder (25 studies) 7 , 12 , 15 , 16 , 18 , 20 , 37 , 40 , 44 , 45 , 49 , 51 , 53 , 54 , 56 , 63 , 76 , 77 , 81 , 82 , 88 , 90 - 92 , 110 , the hip (3 studies) 43 , 50 , 85 , the ankle (1 study) 14 , and basic general arthroscopic skills (6 studies)…”
Section: Resultsmentioning
confidence: 99%
“…Hand-motion analysis can generate a sophisticated data profile that can detect subtle improvement in surgical performance, and may be able to measure the attainment of mastery. Other motion parameters, such as gaze tracking 6 , triangulation time 74 , instrument path length 12 , 15 , 40 , 48 , 49 , 51 , 55 , 56 , 63 , 110 , and collisions 38 , 55 , have demonstrated construct validity and feasibility in the simulated environment but are unlikely to be useful in the live operative theater, as most of these measurements are derived from the simulator itself.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated the construct validity of simulators by showing a correlation between a surgeon's experience and their performance on a simulator. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The procedures where this has been reported include diagnostic and therapeutic knee, hip and shoulder arthroscopy, hip fracture fixation, the fixation of complex intra-articular fractures and basic orthopaedic skills, including drilling (Table II). Studies assessing learning curves.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, institutions and areas such as orthopedics, which understand the need to implement the simulation in their curriculum program design their own simulators, as is the case of arthroscopy simulators and virtual reality programs; however, they must be validated to demonstrate that their design and applicability recreate situations similar to the real ones and that the appropriate process of meaningful learning takes place. [13][14][15][16][17][18][19] Another use of clinical simulation within the orthopedic area is to classify the level of competence of different procedures performed by physicians through performance metrics that precisely define the performance threshold, opening the possibility of using the simulation to evaluate or certifying the level of competence. 20,21 These are lots of simulation approaches in orthopedics; although it is known that orthopedic education in the postgraduate area has great relevance, within the area of undergraduate general medical training is limited, and the evidence found regarding competencies in orthopedics, existing reports show that they lack the skills needed to diagnose, treat or to refer to the specialist.…”
Section: Discussionmentioning
confidence: 99%